The Effect of Motivation, Competence, Compensation on Employee Performance with Organizational Culture as A Moderating Variable - Arsani, Mohammad; Syahyunan, Syahyunan; Fauzan Azhmy, Muhammad (JMET: Journal of Management Entrepreneurship and Tourism, 2025)
Motivation, Competence, Compensation, and Organizational Culture have a great influence on the Employee Performance of PT. Adi Dharma Abadi. These four variables prove that this study aims to analyze the influence of motivation, competence, and compensation on employee performance with organizational culture as moderating variables in PT. Adi Dharma Abadi Bogor Regency. The study was conducted at PT. Adi Dharma Abadi Bogor Regency took 35 employees as the research sample, which was calculated using an equation formula through an interaction test often referred to as Moderated Regression Analysis (MRA) with a total population of 35 employees at an error margin of 2.5 %, for the data collection techniques, questionnaires, interviews, and observations. The data is processed using the SPSS version 26 application. The test data used in this research are reliability tests, validity tests, statistical tests, and classical assumption tests. The results of this study show that Motivation, Competence, Compensation, and Organizational Culture have a positive and significant influence on Performance.